REGULATIONTAX CRIMINAL OFACTION AGAINST CORPORATION IN THE DEVELOPMENT CONTEXT OF TAX CRIMINAL DELICT IN INDONESIA - Galenso Syarif, Vidi (Awang Long Law Review, 2021)
Taxation Crime is in the perspective of material criminal law discussing 3 (three) main problems, namely the formulation of tax crime, tax liability and tax crime solutions. The formulation policy regarding tax crimes is formulated in Articles 38, 39, 39A, 40, 41, 41A, 41B, 41C, 43 and Article 43A, from the formulation of these articles the types of tax crime in the form of violations (culpa) are acts that are not intentionally and a tax crime in the form of a crime (dolus) as an act committed intentionally. Subjects of tax crime are humans and corporations (legal entities). Tax criminal responsibility committed by humans is based on culvability (mistakes), for corporations as tax crime perpetrators, the principle of tax liability is based on the theory of identification, vicarious liability, and strict liability. Criminal sanctions against the tax crime perpetrators only use imprisonment and imprisonment. In order to safeguard state revenues, the formulation of fines against perpetrators of taxation by taxpayers is the main sanction (premum remedium), while imprisonment is formulated as an ultimum remedium (ultimate weapon) sanction. In principle, corporate criminal responsibility in the field of taxation is based on the theory of direct corporate criminal liability, because tax crimes cannot be committed solely on the initiative of corporate employees, but must be on orders from the directing mind or the organ of controlling the corporation. Regarding criminal acts in the field of taxation, the authorities as investigators are certain Civil Servants within the Directorate General of Taxes.